Institutional Effects on National Health Insurance Digital Platform Development and Use: The Case of Ghana - Renner-Micah, A.; Effah, J.; Boateng, R. (Springer Nature Switzerland AG 2020, 2020)
The purpose of this study is to understand institutional effects on digital platform development and use for national health insurance in a developing country. Information systems research on digital platforms for the health sector has focused more on healthcare. Less research exists on health insurance. This study, therefore, addresses the research gap by focusing on digital platform for national health insurance service in a developing country. The study employs qualitative, interpretive case study as methodology and institutional theory as analytical lens to investigate regulative, normative, and cultural-cognitive institutional effects on digital platform development and use for national health insurance in Ghana. The findings show the institutional enablers as: (1) health-seeking culture; (2) mobile network penetration and use; and (3) appropriate laws and regulations. Conversely, the constraints are (1) Unstructured supplementary service data (USSD) functionality; and (2) extended family system.
Research Article
Keywords: Digital platform; Mobile platform; Institutional theory; Health insurance; Interpretive case study; Developing country; Ghana